Comprehensive insights into herbicide resistance mechanisms in weeds: a synergistic integration of transcriptomic and metabolomic analyses - Sen, Madhab Kumar; Bhattacharya, Soham; Bharati, Rohit; Hamouzová, Katerina; Soukup, Josef (Frontiers in Plant Science, 2023)
Omics techniques, including genomics, transcriptomics, proteomics, and metabolomics have smoothed the researcher's ability to generate hypotheses and discover various agronomically relevant functions and mechanisms, as well as their implications and associations. With a significant increase in the number of cases with resistance to multiple herbicide modes of action, studies on herbicide resistance are currently one of the predominant areas of research within the field of weed science. High-throughput technologies have already started revolutionizing the current molecular weed biology studies. The evolution of herbicide resistance in weeds (particularly via non-target site resistance mechanism) is a perfect example of a complex, multipathway integration-induced response. To date, functional genomics, including transcriptomic and metabolomic studies have been used separately in herbicide resistance research, however there is a substantial lack of integrated approach. Hence, despite the ability of omics technologies to provide significant insights into the molecular functioning of weeds, using a single omics can sometimes be misleading. This mini-review will aim to discuss the current progress of transcriptome-based and metabolome-based approaches in herbicide resistance research, along with their systematic integration.